EVALUATING THE IMPACT OF EMOTIONAL FREEDOM TECHNIQUE (EFT) ON POST-CESAREAN SECTION PAIN MANAGEMENT: A CASE STUDY AT JEMURSARI ISLAMIC HOSPITAL, SURABAYA - Maiisa, Khotimatul Chusna; Afiyah, R. Khairiyatul; Umamah, Farida; Kartini, Yanis (Universitas Nahdlatul Ulama Surabaya, 2024)
Introduction: Problems that arise during post-cesarean section procedures due to incisions caused by tearing of the abdominal wall tissue and uterine wall can cause changes in continuity so that the mother feels pain due to the surgery. Objective: This study analyzes the impact of the Emotional Freedom Technique (EFT) therapy on managing post-cesarean section pain in a patient at Jemursari Islamic Hospital, Surabaya. Methods: The research employed a case study design focusing on a single patient, Mrs. M, with acute post-operative pain. Data collection methods included assessment, observation, anamnesis, and interviews. The EFT intervention was administered once daily for three consecutive days, with each session lasting 30 minutes. Results: The results indicated a reduction in pain intensity from a score of 4 to 2 on the pain scale. Conclusions: While these findings suggest that EFT may be an effective non-pharmacological pain management tool, the study’s limitations—including the small sample size and absence of a control group—necessitate further research with larger, controlled trials to validate these results.